Internet Based Infertility Information in Bahasa Indonesia Quality Survey - Andon Hestiantoro; Intan Kusumaningtyas (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: To assess the quality of websites providing informationon infertility and its management in Bahasa.Methods: Differences between website types and affiliates wereassessed for the credibility, accuracy and ease of navigation usingpredefined criteria. We used Google search engine with the keyword"infertilitas" and we assessed 50 websites in Bahasa that relates withinfertility.Results: The content credibility for most of the sites has adequatescore with range of score 60 to 80 for 68% sites. Content accuracyfor most of the sites have scores more than 60, with 24% or 12sites with scores 60 to 80 and 44% or 22 sites have scores above80. The ease of navigation for most of the sites, 47 sites or 94%has scores more than 60.Conclusion: The quality of internet based infertility information inBahasa is adequate for category credibility, accuracy and ease ofnavigation.[Indones J Obstet Gynecol 2018; 6-1: 28-33]Keywords: bahasa, infertility, information, internet, quality